Clostridial myonecrosis in association with etoposide therapy presenting as severe thigh pain. Issue 727 (May 1986) - Smith, D.; Harris, M.; Thatcher, N.
Abstract : The case is described of a 68 year old man who was immunosuppressed as a result of receiving chemotherapy for small cell lung cancer and who presented with severe right thigh pain. This proved to be due to clostridial myonecrosis with none of the classical clinical features of clostridial infection. This is believed to be the first reported case of spontaneous clostridial infection associated with etoposide administration.